Advances in research of DNA damage and repair in cells exposed to various types of ionizing radiation in the era of super-resolution optical microscopy - Falk, Martin; Hausmann, Michael (Casopis lekaru ceskych, 2020)
The present work introduces new findings about the influence of different radiation types on the cells, with the concern on the micro- and nanodosimetric aspects of chromatin damage. Emphasized is the relationship between the physical parameters of the incident radiation (g-rays, protons and high-LET heavy ions), character of chromatin damage, ability of cells to repair and survive DNA damage, and risk of genetic changes. While confirming a positive correlation between the LET of ionizing radiation, complexity of induced DNA double-strand breaks (DSB), and biological effectiveness (RBE) of radiation, at the same time, we show that our understanding of this relationship is only incomplete. Our discovery that various accelerated ions with similar LET can damage DNA in different ways and kill cells with unequal efficiency, could serve as an example. In addition, many aspects of DSB repair remain to be explained, for instance, how the cell activates the particular repair pathway at sites of individual DSBs, and how it depends on the radiation used and the chromatin architecture. The discussed results may be important, above all, for newly developing hadron therapy and in the context of manned interstellar flights planning. From the methodological point of view, we point to a tremendous progress in the field of optical microscopy and its research applications. In more detail, we introduce single-molecule localization microscopy (SMLM).
Keywords: ionizing radiation of different types; ionizující záření; poškození DNA; single-molecule localization microscopy (SMLM).; super-resolution microscopy; Microscopy; Radiation, Ionizing; chromatin architecture; lidé; mikroskopie; DNA Damage; dvouřetězcové zlomy DNA; DNA Breaks, Double-Stranded; Humans; DNA radiation damaging and repair; ionizing radiation-induced foci (IRIF)